Mission command and philosophy for the 21st century. Issue 2 (3rd March 2020) - Ploumis, Michail
Abstract: In an effort to strengthen the principal tenet of shared understanding in mission command, the following article advocates the selective teaching of philosophy be included in the training of military commanders. The article introduces a brief but relevant philosophical context, from Plato to Machiavelli, to distinguish both the potency of liberal education and its ability to develop shared understanding and trust between commanders. The evolving landscape of military operations in the Information Age entails a growing need for officers to think critically and act quickly, thus lending authority to the argument that philosophical understanding can eliminate potential shortcomings of otherwise inadequately implemented mission command.